Deriving macroeconomic benefits from public-private partnerships in developing Asia - Minsoo Lee; Xuehui Han; Raymond Gaspar; Emmanuel Alano (Asian Development Bank (ADB), 2018)
The provision of infrastructure and related services in developing Asia via publi-private partnership (PPP) increased rapidly during the late 1990s. Theoretical arguments support the potential economic benefits of PPPs, but empirical evidence is thin. This paper develops a framework identifying channels through which economic gains can be derived from PPP arrangement. The framework helps derive an empirically tractable specification that examines how PPPs affect the aggregate economy. Empirical results suggest that increasing the ratio of PPP investment to GDP improves access to and quality of infrastructure services, and economic growth will potentially be higher. But this optimism is conditional, especially on the region's efforts to further upgrade its technical and institutional capacity to handle complex PPP contracts.
Keywords: H54; O11; O18; O47; 330; developing Asia; economic growth; infrastructure; poverty reduction; public-private partnership